Formal Synthesis of Pseudolaric Acid B - Mori, Naoki (Synlett, 2020)
A formal synthesis of pseudolaric acid B, a diterpene isolated from the root bark of Pseudolarix kaempferi Gordon (Pinaceae), to Trost’s synthetic intermediate was achieved in 17 steps from a known ketone. Key features of this synthesis include a Claisen rearrangement and iodoetherification to construct quaternary stereocenters and ring-closing metathesis to form the seven-membered ring.
Keywords: pseudolaric acid B; total synthesis; diterpenes; cytotoxins; Claisen rearrangement; iodoetherification